Progress of researches on inducing hepatic stellate cell ferroptosis for treatment of liver fibrosis - SUN Lijie, HAO Dandan (Jichu yixue yu linchuang, 2024)
Emerging evidence suggests that ferroptosis, an iron-dependent form of regulated cell death, plays a critical role in the genesis of liver fibrosis through inducing hepatic stellate cell (HSC) ferroptosis to inhibit liver fibrosis or inducing hepatic ferroptosis to potentiates liver fibrosis. Pharmacologically targeting at ferroptosis with its inducers can slow down the progression of liver fibrosis in vitro and in vivo model. This review suggests that pharmacological induction of HSC ferroptosis might be used as a potential novel targeted therapy for the treatment of liver fibrosis.